3rd World Congress of GI Endoscopy to take place in Japan, May 2022. (1st March 2021) - Emura, Fabian; Tajiri, Hisao
Abstract : Looking forward to the next global conference from the World Endoscopy Organization, in partnership with the Japan Gastroenterological Endoscopy Society